Presumptive non‐cirrhotic bleeding esophageal varices in a dog. (14th September 2018) - Myers, Marc; Scrivani, Peter V.; Simpson, Kenneth W.
Abstract : An 8‐year‐old male American Staffordshire terrier was admitted for evaluation of chronic episodes of ptyalism and hematemesis after exercise. Abnormalities were not detected on routine clinicopathological tests, thoracic radiography, and abdominal ultrasonography. Endoscopic examination revealed a labyrinthine network of severely distended, hemorrhagic esophageal blood vessels. Computed tomography angiography demonstrated a network of para‐esophageal vessels that communicated with the celiac artery caudally and the brachiocephalic trunk cranially, consistent with a diagnosis of non‐cirrhotic esophageal varices. This is a report of exercise, ptyalism, and hematemesis secondary to presumptive, non‐cirrhotic, bleeding esophageal varices in a dog.